Non-contact method used to determine the swelling/shrinking coefficients under CO2 sorption/desorption on an HNBR O-ring - Study of coupling with temperature and pressure. (May 2020) - Lainé, E.; Grandidier, J.C.; Benoit, G.; Omnès, B.; Boyer, S.A.E.
Abstract: To make use of an O-ring under different pressures and temperatures and to procedure predictive numerical simulations of its use, it becomes important to identify the O-ring behavior under coupled CO2 sorption (i.e. swelling) and desorption (i.e. shrinking) together with the effect of temperature. Therefore, the presented study deals with an experimental non-contact measurement technique to identify the swelling and shrinking coefficients during pressurization and depressurization under carbone dioxide (CO2 ) of an HNBR O-ring. In order to ensure the feasibility of CO2 sorption (or desorption) measurement from the non-contact method, a purely thermal expansion test permits to identify the thermal expansion coefficient of HNBR, which is well known by other methods including a standard. Numerical simulations complete this section. The simulations ensure that the chosen analysis methodology allows direct identification of swelling and shrinking coefficients and thus determine the seal volume change. CO2 pressurization and CO2 depressurization tests at pressures (2, 4 and 6 MPa) under isothermal conditions (60 and 130 °C) and a coupled temperature-pressure CO2 tests are conducted. The measurements made during these tests show that the CO2 swelling and shrinking coefficients are independent of pressure but temperature dependent. Besides, a good measurements reproducibility was observed and the order of magnitude of these coefficients leads to a strain in the same order as the thermal strain. Highlights: This method permits to characterize the material used in the structure obtained with industrial process. In order to measure the swelling of an elastomer seal under conditions, an in situ optical measurement system is used. Pressurization and depressurization tests under CO2 and a coupled temperature-pressure CO2 test are carried out. Non-contact measurement method is validated in a thermal expansion test. The CO2 sorption and desorption coefficients are independent of pressure but dependent on temperature.